2013
DOI: 10.1002/anie.201206817
|View full text |Cite
|
Sign up to set email alerts
|

Triazine‐based Carbon Nitrides for Visible‐Light‐Driven Hydrogen Evolution

Abstract: A new dimension: The doping of amorphous poly(triazine imide) (PTI) through ionothermal copolymerization of dicyandiamide with 4-amino-2,6-dihydroxypyrimidine (4AP) results in triazine-based carbon nitrides with increased photoactivity for water splitting compared to crystalline poly(triazine imide) (PTI/Li(+)Cl(-), see picture) and melon-type carbon nitrides. This family of carbon nitride semiconductors has potential as low-cost, environmentally clean photocatalysts for solar fuel production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
326
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(346 citation statements)
references
References 38 publications
13
326
0
4
Order By: Relevance
“…Hence, organocatalysts have attracted the interests of many researchers during the last decades. However, organocatalysts have mainly been based on two types of organic materials: organometallic complexes, [1] in which the metallic composition may limit their practical applications due to high cost, potential toxicity, and poor sustainability; or covalent organic polymers, including commonly reported carbon nitride, [2,3] triazine/hydrazone-based carbon nitrides, [4][5][6][7] and some covalent organic polymers based on poly(p-phenylene), [8,9] poly(phenyleneethinylene), [10] poly(diph enylbutadiyne), [11] poly(azomethine), [12] and carbazolic frameworks. [13] However, non-covalent self-assembly supramolecular systems composed of purely organic molecules alone, working as a photocatalyst with wide visible-light responses has not been reported.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 99%
“…Hence, organocatalysts have attracted the interests of many researchers during the last decades. However, organocatalysts have mainly been based on two types of organic materials: organometallic complexes, [1] in which the metallic composition may limit their practical applications due to high cost, potential toxicity, and poor sustainability; or covalent organic polymers, including commonly reported carbon nitride, [2,3] triazine/hydrazone-based carbon nitrides, [4][5][6][7] and some covalent organic polymers based on poly(p-phenylene), [8,9] poly(phenyleneethinylene), [10] poly(diph enylbutadiyne), [11] poly(azomethine), [12] and carbazolic frameworks. [13] However, non-covalent self-assembly supramolecular systems composed of purely organic molecules alone, working as a photocatalyst with wide visible-light responses has not been reported.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 99%
“…The most well-known of these photocatalysts are the inorganic solids [1][2][3]6], mostly oxides but also sulfides and selenides, the former including titanium dioxide [13][14][15], the quintessential photocatalyst. Perhaps less well-known, a range of supramolecular systems [16,17] and even organic polymers [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have also been reported to act as photocatalysts. In this mini-review we will discuss computational work on modelling such photocatalysts in terms of the relevant material properties and processes, as well as what we believe to be key aspects to consider when performing such calculations.…”
Section: Which States That Photocatalysis Is the 'Change In The Rate mentioning
confidence: 99%
“…42,47,48 The use of the starting monomer DCDA in LiBr/KBr molten mixture leads to form TGCN at 600°C for 60 h. 41 Theoretical investigation on TGCN indicates that this material is a direct band-gap semiconductor with an optical bandgap of 2.0 eV at AB-stacking arrangement, however, an optical band gap of less than 1. showed that CTFs can be synthesized through an organic synthetic route using an acid catalyst. 49 In these reports, semiconducting properties of CTFs are investigated by UVvis spectroscopy and photoluminescence properties.…”
Section: Synthesis and Applications Of Ctfsmentioning
confidence: 99%